Studies in the mechanism of the gasification of carbon in pulsed blast producer - Cruz, Ibarra E.
Evidence of the feasibility of the pulsed gasificationprocess and its attendant advantages over the conventional method of gasifying with a steady blast, is provided by: (i) theoretical thermodynamic and kinetic studies aided by a critical appraisal of previous work on combustion and gasification reactions; (ii) proving experiments on the atmospheric gasification of coke.
A theretical thermodynamic study involving a new graphical method for calculation equilibrium gas sompositions, and kinetic calculations based on available data on reaction rates of carbon with air or steam, indicated that: (a) steam decomposition and thermal efficiency could be improved by pulsing; (b) using oxygen and steam, and raising the working pressure would increase the effectiveness of the pulsed process; (c) practical pulsing times of about 30 seconds and 60 seconds respectively for steam and air at normal rates could be used to keep the ignition plane stable.
An experimental study on the reaction kinetics of the gasification of an actual lump of coke suspended in a bench scale reactor furnace, provided empirical rate equations which indicated that calculated pulsing times are reasonably accurate and could even be made longer.
Subsequent gasification experiments on a pilot plant scale showed that: (a) pulsing with air and steam at a pulsing time of 30 seconds for steam and 60 seconds for air, did not result in any migration of the ignition plane; (b) pulsing with oxygen-steam and steam reduced by 30% the optimum steam requirement for clinker control compared with that for the steady-blast producer, as a consequence of which the specific dry yield improved by 60%, the gas calorific value became higher by 25%, and the thermal efficiency increased from 70% to 80%.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Keywords: Thermal efficiency; Steam decomposition